Program Naturalisasi Timnas Sepakbola Indonesia Ditinjau dari Etika Kristen - Pangayow, Laura Meirien Olivia; Hermanto, Yanto Paulus (Misioner, 2025)
The national football federation (PSSI) has recently adopted a policy of naturalising foreign players as a strategic move to strengthen the national team in the face of limited local talent and the low quality of domestic competition. This policy has become a phenomenon that has sparked various discussions, from political, social, and theological perspectives. Through descriptive qualitative methods with literature studies and interviews with five Christian ethicists, this study found that naturalisation is viewed positively when carried out within the framework of love and justice and understood as a means of God's blessing. These values find their theological basis in the story of Ruth, which shows that accepting foreigners can contribute to the faith community. Thus, the naturalisation of football players is not only a legal and sporting strategy issue, but also has important ethical and theological dimensions in nation building.